Analysis of the evolution of the theories behind studies dedicated to a company´s internationalization - Albertoni, Nicolás; Horta, Roberto (Estudios de Administración, 2021)
The main purpose of this article is to analyze the evolution of the theories behind studies related to any company’s internationalization. To do this, we conducted a bibliographic review of the state of research on the subject in peer-reviewed journals and related books. References are made to the concept of internationalization, and a panoramic and systematic review is performed of literature available on theories related to the gradual process of internationalization and to other more aggressive approachesthat speak of ‘non-gradual’ or ‘accelerated’ processes of internationalization. The analysis is complemented with different approaches to - or models for - a company’s internationalization that we felt contributed to the task at hand. The review of this literature is pertinent from a historical perspective since much of the current work on companies’ internationalization has been developed in contexts where the prevailing policy at the global level tended towards the liberalization of trade and not towardsprotectionism. Recent studies analyzed in this article have duly highlighted the need to adapt the course of a company’s internationalization to a more dynamic, systemic and uncertain environment. Ultimately, we examine how determined companies have achieved positive exporting experiences and what are the theoretical bases that explain such phenomena.